Augmented Reality Based Tajwid Reading Law Android Application - Agyztia Premana (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
The learning method used in learning the subjects of the Qur'an and Hadith in Schools is a common teaching method, which uses books as a source of knowledge and teachers as teachers. In this problem, the author uses a learning method using Augmented Reality (AR) as the basic law of reading aloud so that students don't get bored. Augmented Reality (AR) is a combination of real and virtual objects displayed simultaneously on a screen. Augmented Reality is created with Unity 3D, Vuforia and Android software. The application of new learning methods should increase students' interest in serious and straightforward learning. This research aims to build a recitation science learning application for children 5-10 years old using an Android-based device